Congenital insensitivity to pain: Case report of a rare entity - Swati Dahiya; Kondajji Ramchandra Vijayalakshmi; Mubeen Khan (Wolters Kluwer Medknow Publications, 2018)
Hereditary sensory and autonomic neuropathies (HSANs) are a group of disorders characterized by insensitivity to noxious stimuli and autonomic dysfunction, associated with pathological abnormalities of the peripheral nerves. Five types of HSAN have been reported in literature, out of which Type V known as congenital insensitivity to pain (CIP) is a rare autosomal recessive condition. Self-mutilation is an invariable feature of this disorder, involving the teeth and orofacial structures. This case report describes a case of a 6-year-old girl with CIP brought by her parents for prostheses to replace her self-extracted primary teeth.